The influence of hyperglycemia on the safety of ultrasound in retinal pigment epithelial cells. (5th January 2021) - Kang, Heather; Yin, Naibo; Lyon, Heather; Rupenthal, Ilva D.; Thakur, Sachin S.; Mugisho, Odunayo O.
Abstract: Ultrasound (US) assisted drug delivery is receiving interest in treating posterior eye diseases, such as diabetic retinopathy due to its ability to maximize drug penetration into difficult to reach tissues. Despite its promise, the technique has only been investigated using healthy cell and tissue models, with no evidence to date about its safety in active disease. As a result, the aim of this study was to evaluate the safety of US administration in vitro in retinal pigment epithelial cells under normal and high glucose conditions. US protocols within the presently accepted safety threshold were applied and their influence on cell membrane and tight junction integrity as well as intracellular inflammation was evaluated using lactate dehydrogenase (LDH), zona occludens‐1 (ZO‐1), fluorescein isothiocyanate (FITC)‐dextran dye leak and nuclear factor‐kappaB (NF‐κB) assays, respectively. Under high glucose conditions, US application increased LDH release and resulted in loss of ZO‐1 labeling at 2 h; however, normal levels were restored within 24 h. US within its safety parameters did not induce any FITC‐dextran dye leak or NF‐κB nuclear translocation in normal or high glucose conditions. In conclusion, our results suggest that while high glucose conditions increase cell susceptibility to US‐mediated stress, basal conditions can be restored within 24 h without long‐lasting cell damage.